(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
The dynamic nature of the world technology calls on stress in the dire need of Information and Communication Technology (ICT) courses that fulfil the skills needs of the industries. The gap between ICT education and employee level competencies required by employers to secure employment and economic growth in the region by the Enugu State of Nigeria still exists. In this paper, the integration of machine learning (ML) into curriculum development in ICT is considered to create a model of an educational process that is dynamic and industry-specific. As part of an elaborate study of the secondary data including the educational policies, industry reports and academic studies, the research indicates the problem in the immediate form of obsolete curriculum, ineffective infrastructure and lack of training of teachers. It implies a responsive curriculum proposal that incorporates ML to tailor learning, enhance the skill acquisition process as well as closing the gap between academia and industry. Another constraint that can limit the implementation is also addressed in the article; it includes resources constraint and stakeholder resistance; practical solution to the implementation is also given. This is an endeavor to empower resources to increase sustainable development by aligning the ICT with the needs of the increasing tech environment in Enugu by educating students, teachers, and policymakers.